Examples with solutions for Extracting Square Roots: Applying the formula

Exercise #1

Solve for X:

xx=49 x\cdot x=49

Video Solution

Step-by-Step Solution

We first rearrange and then set the equations to equal zero.

x249=0 x^2-49=0

x272=0 x^2-7^2=0

We use the abbreviated multiplication formula:

(x7)(x+7)=0 (x-7)(x+7)=0

x=±7 x=\pm7

Answer

±7

Exercise #2

Solve the following exercise:

2x28=x2+4 2x^2-8=x^2+4

Video Solution

Step-by-Step Solution

First, we move the terms to one side equal to 0.

2x2x284=0 2x^2-x^2-8-4=0

We simplify :

x212=0 x^2-12=0

We use the shortcut multiplication formula to solve:

x2(12)2=0 x^2-(\sqrt{12})^2=0

(x12)(x+12)=0 (x-\sqrt{12})(x+\sqrt{12})=0

x=±12 x=\pm\sqrt{12}

Answer

±12 ±\sqrt{12}

Exercise #3

Solve the following equation:

x216=x+4 x^2-16=x+4

Video Solution

Step-by-Step Solution

Please note that the equation can be arranged differently:

x²-16 = x +4

x² - 4² = x +4

We will first factor a trinomial for the section on the left

(x-4)(x+4) = x+4

We will then divide everything by x+4

(x-4)(x+4) / x+4 = x+4 / x+4

x-4 = 1

x = 5

Answer

5

Exercise #4

Solve the following exercise:

x220=5 x^2-20=5

Video Solution

Answer

±5

Exercise #5

Solve the following equation:


2x28=x2+4 2x^2-8=x^2+4

Video Solution

Answer

±12 ±\sqrt{12}

Exercise #6

Solve the following exercise

x3x+7=2x2+9 x\cdot3\cdot x+7=2x^2+9

Video Solution

Answer

±2 ±\sqrt{2}

Exercise #7

Solve the following:

x2+x23=x2+6 x^2+x^2-3=x^2+6

Video Solution

Answer

±3

Exercise #8

Solve the following equation:

4x2+8+2x=x+12+x 4x^2+8+2x=x+12+x

Video Solution

Answer

±1

Exercise #9

Solve the following equation:

x236=6x36 x^2-36=6x-36

Video Solution

Answer

0 or 6 0~or~6